INFLUENCE OF PREVIOUS MOTOR EXPERIENCE ON ATTITUDES ABOUT SERVICE-LEARNING AMONG STUDENTS - Miletić, Đurđica; Jadrić, Ivana; Miletić, Alen (Sport - nauka i praksa, 2023)
Service-Learning (SL) as a growing innovative pedagogical model, has recently become more popular in higher education area dedicated to physical activity. Since physical education (PE) students are oriented toward society, it is extremely important for them to develop a sense of connection and responsibility toward society during their studies. This research was carried out on a sample of 58 students of a PE study program, aged between 20 and 22. The first step of the research was to determine six different groups of students using the poly-structured interview about their previous motor experience while considering the type of activity, the length of time engaged in a certain activity and the level of motor skills. Six investigated groups were formed according to their dominant previous motor activity: artistic and aesthetic activities, society-oriented recreational activities, self-directed recreational activities, team sports, individual sports, and martial arts. In order to determine the students’ perception of SL Benefits, the SELEB questionnaire was used. The original 27 items generated for the SELEB scale that measure the benefit categories were divided into six categories: civic responsibility, interpersonal skills, leadership ability, ability to apply knowledge, general life skills and critical thinking. One-way Analysis of Variance was used to analyse the differences in investigated groups defined by previous motor experience on SL attitudes among students. The results showed significant differences between groups in SL experience (F5,52 = 3,19; p=0,014). The highest value on the SELEB scale was recorded in the group with dominant artistic and aesthetic activities, and the lowest value on the SELEB scale was recorded in a group with dominant previous experience in individual sports. Significant differences were determined with the post-hoc Tukey HSD test between groups with minimal previous experience in individual sports and groups with dominant previous experience in society-oriented recreational activities, team sports, and artistic/aesthetic activities.
Keywords: SELEB scale; Sustainable Development Goals; physical activities